Multi-objective optimization of methionine+cysteine levels in diets for growing pigs - José L. Figueroa-Velasco (Universidad de Antioquia, 2020)
Background: The addition of synthetic methionine to growing pig diets should consider the requirements of the methionine+cysteine complex, as most cysteine is obtained through dietary methionine. Objective: To determine an optimal level of methionine+cysteine (Met+Cys) in growing pig diets. Methods: Ninety-nine hybrid (Yorkshire×Landrace×Duroc) barrows were used in a completely randomized design (initial body weight: 25.90±3.99 kg). Nine levels of Met+Cys (0.500, 0.525, 0.550, 0.575, 0.600, 0.625, 0.650, 0.675, and 0.700%) were evaluated during 35 days. To determine a multi-objective optimal level of Met+Cys, growth performance and strongly related carcass traits were evaluated. Results: Average daily feed intake (ADFI) and feed:gain ratio (FGR) showed a linear response to the dietary Met+Cys level (p<0.05), with estimated optimal concentration at 0.700%. Average daily gain (ADG) did not show any effect on the Met+Cys level (p>0.05). Carcass characteristics were not affected by the Met+Cys concentration (p>0.05). The multi-objective optimal level for ADG, ADFI, and FGR was 0.667% Met+Cys. Conclusions: According to our results, 0.667% Met+Cys is the best concentration in diets for growing pigs.